(untitled) (Eurasian Medical Research Periodical, 2022)
Coronavirus infection (COVID-19) is an infectious disease characterized by a relatively high contagiousness and the likelihood of developing severe complications in the form of acute respiratory distress syndrome, acute respiratory and multiple organ failure. The pathogenesis of coronavirus infection has not been studied enough, it has been spreading around the world for the second year. The virus is neurotropic and can directly damage brain structures such as the limbic system and hypothalamus